Сутнісна характеристика мотиваційного механізму ефективного використання людського капіталу будівельного підприємства - Лич, В. М.; Малихіна, О. М. (Ways to Improve Construction Efficiency, 2012)
On the basis of existing approaches to the determination of the motivation mechanism of effective human capital usage its essence character is given, taking into consideration the peculiarities of the reproduction of construction enterprises labor potential. The work determines the principles structure, elements end determination of the motivation mechanism in the process of its development.